Composite coating suitable for platinum or platinum-rhodium alloy and preparation method and application thereof

By spraying a composite coating containing zirconia, yttrium oxide, cerium oxide and silica on the surface of platinum or rhodium alloys, the oxidation and bubble problems in high temperature environments are solved, the antioxidation ability is improved, and glass defects are avoided and cost increases.

CN119306493APending Publication Date: 2025-01-14SICHUAN SHUWANG CHENSHENG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411485510.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

During the glass production process, platinum or platinum-rhodium alloy parts react with oxygen under high temperature environments, causing oxide volatility and bubble generation, resulting in internal defects of the glass and increased production costs. It is difficult for the prior art to effectively avoid these problems.

Method used

Using a composite coating, including 82.5-97.5% zirconia, 0.5-9.2% yttrium oxide, 0.3-8.7% cerium oxide, 0.5-2% sodium oxide and 0.2-2.1% silica, by Preparation of ball milling and screening, sprayed on the surface of platinum or rhodium alloys, using zirconium oxide as thermal insulation agent, yttrium oxide and cerium oxide as stabilizers, sodium oxide and silica as modifiers, to form high density coating.

Benefits of technology

It effectively improves the oxidation resistance of platinum or platinum-rhodium alloy parts, avoids the occurrence of platinum/rhodium defects in glass, extends the service life of the equipment and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098613600000041
    Figure BDA0005098613600000041
  • Figure BDA0005098613600000042
    Figure BDA0005098613600000042
  • Figure BDA0005098613600000051
    Figure BDA0005098613600000051
Patent Text Reader

Abstract

The invention discloses a composite coating suitable for platinum or platinum-rhodium alloy and a preparation method and application thereof, and relates to the technical field of glass production. According to the technical scheme, the composite coating is prepared from the following components in percentage by mass in terms of oxide: 82.5 to 97.5 percent of ZrO2, 0.5 to 9.2 percent of Y2O3, 0.3 to 8.7 percent of CeO2, 0.5 to 2 percent of Na2O and 0.2 to 2.1 percent of SiO2. After the surface of the platinum or platinum-rhodium alloy part is coated with the composite coating, glass cannot be polluted, the oxidation resistance of the platinum or platinum-rhodium alloy part is improved, platinum / rhodium defects in the production process of optical glass and electronic glass are effectively avoided, the operation period of the platinum or platinum-rhodium alloy part is obviously prolonged, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass production, and in particular to a composite coating suitable for platinum or platinum-rhodium alloy, and a preparation method and application thereof. Background Art

[0002] Optical glass and electronic glass have extremely high quality requirements due to the special nature of their applications, especially strict restrictions on their internal defects: bubbles, stones and platinum / platinum-rhodium defects. In order to improve the quality of glass, the melting furnace is equipped with a platinum system (platinum / platinum-rhodium alloy parts), which includes a clarification device, a homogenization device, a cooling device and a feed pipe. The production process temperature of optical glass and electronic glass is in a high temperature environment of 1200-1600℃. Under long-term high temperature environment, the platinum or platinum-rhodium alloy parts of the platinum system will react with oxygen in the air or oxygen in the glass to generate platinum oxide or platinum-rhodium oxide gas. After the volatilization of this part of gas, the platinum or platinum-rhodium alloy will be lost, which directly causes the strength and stability of the platinum system to be damaged, affecting the service life. Since the volatile platinum oxide or platinum-rhodium oxide will adhere to the refractory materials, insulating materials and cold spot areas of the platinum channel where there is a free liquid surface in the platinum channel system, this part of the platinum oxide or platinum-rhodium alloy oxide will form triangular, hexagonal or needle-shaped crystals under specific conditions. When the environment fluctuates, they will fall into the glass to form precious metal foreign body defects, affecting the quality of the glass and increasing production costs.

[0003] Secondly, secondary bubbles will be generated in the platinum system under high temperature for a long time. The generation of these bubbles is mainly affected by factors such as the thermoelectric electrolysis of the melt, the decomposition of the oxide clarifier and the number of OH groups dissolved in the glass liquid, among which the number of OH groups has a particularly great impact. The platinum system reacts with the OH groups in the glass liquid at high temperature, and the OH groups in the glass liquid decompose into neutral hydrogen and oxygen. Hydrogen can penetrate through the outer skin of platinum or platinum-rhodium alloy parts, while oxygen is enriched on the surface of the glass liquid. When the oxygen concentration exceeds the solubility limit of the glass liquid, secondary bubbles will be formed, that is, hydrogen permeation and oxygen evolution will occur, resulting in defective products.

[0004] Therefore, there is an urgent need for a composite coating which, when applied to the surface of platinum or platinum-rhodium alloy parts, will not contaminate the glass but can improve the antioxidant capacity of the platinum or platinum-rhodium alloy parts, effectively avoid the generation of platinum oxide or platinum-rhodium oxide, bubbles and stone defects in the production process of optical glass and electronic glass, improve production efficiency, and at the same time extend the operating life of platinum or platinum-rhodium alloy parts and reduce production costs. Summary of the invention

[0005] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide a composite coating suitable for platinum or platinum-rhodium alloy, and a preparation method and application thereof; after the composite coating of the present invention is coated on the surface of a platinum or platinum-rhodium alloy part, it will not pollute the glass and improve the antioxidant capacity of the platinum or platinum-rhodium alloy part, effectively avoiding the generation of platinum / rhodium defects in the production process of optical glass and electronic glass, significantly extending the operating life of the platinum or platinum-rhodium alloy part, and reducing the production cost.

[0006] The technical solution of the present invention is:

[0007] In a first aspect, the present invention provides a composite coating suitable for platinum or platinum-rhodium alloy. Calculated as oxides, the composite coating comprises the following components in percentage by mass: 82.5-97.5% ZrO2, 0.5-9.2% Y2O3, 0.3-8.7% CeO2, 0.5-2% Na2O, and 0.2-2.1% SiO2.

[0008] Among them, the introduction of Na2O and SiO2 can be Na2CO3, Na2SO4, silicon dioxide or Na2Si2O5.

[0009] Preferably, the mass percentage of ZrO2 is 85-96%, the mass percentage of Y2O3 is 0.8-7.5%, the mass percentage of CeO2 is 0.5-6.1%, the mass percentage of Na2O is 0.7-1.6%, and the mass percentage of SiO2 is 0.5-1.5%.

[0010] Preferably, the mass ratio of the total mass of Na2O and SiO2 to Y2O3 is less than 1, and the sum of the mass percentages of Y2O3 and CeO2 is less than 10%.

[0011] In the coating composition of the present invention, considering the density and strength of the composite coating, the particle size of each component is 1-30 μm; preferably, the particle size of each component is 3-15 μm. If the particle size is too large, the density of the coating is low and the distribution is uneven; if the particle size is too small, the function of enhancing the strength of the coating will be lost.

[0012] In a second aspect, the present invention provides a method for preparing the above-mentioned composite coating suitable for platinum or platinum-rhodium alloy, comprising the following steps:

[0013] S1 weighs the raw materials and puts them into a mixer for thorough mixing;

[0014] S2 weighs the fully mixed mixture, puts it into a material tank, uses grinding balls, drops anhydrous ethanol into it, and puts it into a ball mill for ball milling;

[0015] S3 takes the ball-milled mixture and screens it to obtain a composite coating suitable for platinum or platinum-rhodium alloy.

[0016] Preferably, in step S2, the ball milling speed is 300-500 rpm, and the ball milling time is ≥120 min.

[0017] In a third aspect, the present invention provides an application of the above-mentioned composite coating suitable for platinum or platinum-rhodium alloy, wherein the composite coating is sprayed on the surface of a platinum or platinum-rhodium alloy part, and the temperature of the platinum or platinum-rhodium alloy part is 500-750°C.

[0018] Preferably, after spraying, the platinum or platinum-rhodium alloy part is kept at 1000-1100° C. for 140-160 min, and then cooled to room temperature at a rate of 2-3° C. / h.

[0019] Preferably, the spraying thickness of the composite coating is 0.05-0.4 mm.

[0020] In the composite coating of the present invention, ZrO2 is coated on the surface of the platinum / platinum-rhodium alloy part, which can play the role of heat insulation and oxygen isolation for the base material, thereby reducing the oxidation damage of the platinum / platinum-rhodium alloy part under high temperature conditions, and at the same time reducing the erosion of the glass under high temperature conditions. When ZrO2 is used alone, it will produce phase change with the change of temperature, accompanied by the change of volume, which accelerates the peeling of the coating. Therefore, the present invention uses Y2O3 as a stabilizer, which is melted into the ZrO2 lattice under high temperature conditions, and can effectively improve the stability and service life of the composite coating. The role of CeO2 is similar to that of Y2O3. Using CeO2 as a stabilizer, it is melted into the ZrO2 lattice under high temperature conditions to fill the internal pores of the coating to obtain a high-density CeO2-stabilized ZrO2 coating, which can solve the problem of low density and uneven distribution of the coating when ZrO2 is used alone. Na2O is used as a modifier in combination with SiO2. Under high temperature conditions, the two react to form Na2Si2O5, which is further melted to fill the internal gaps of the coating to obtain a highly dense CeO2 / Y2O3 stabilized ZrO2 coating, which can solve the problem of low density and uneven distribution of the coating when ZrO2 is used alone.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The composite coating of the present invention selects zirconium oxide, cerium oxide, yttrium oxide, sodium oxide and silicon dioxide with specific component contents, and combines with the substrate by utilizing the bonding effect of the molten composite phase at high temperature, thereby reducing the corrosion of the substrate and achieving the purpose of protecting the substrate. After the composite coating of the present invention is applied to the surface of the platinum or platinum-rhodium alloy part, it will not pollute the glass and improve the anti-oxidation ability of the platinum or platinum-rhodium alloy part, effectively avoiding the generation of platinum / rhodium defects in the production process of optical glass and electronic glass, improving production efficiency, and reducing the volatilization of the platinum or platinum-rhodium alloy part under high temperature conditions, significantly extending the operating period of the platinum or platinum-rhodium alloy part, and reducing production costs. DETAILED DESCRIPTION

[0023] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0024] The preparation method of the composite coating of the following embodiment is as follows:

[0025] S1 Weigh zirconium oxide, yttrium oxide, cerium oxide, sodium carbonate and silicon dioxide respectively and put them into a double-motion flying knife dispersing mixer for thorough mixing;

[0026] S2 weighs the mixed material after thorough mixing, puts it into a polytetrafluoroethylene material tank, uses zirconium grinding balls, drops 10mL of anhydrous ethanol, puts it into a planetary ball mill, sets the ball milling speed to 380rpm, and the ball milling time to 150min;

[0027] S3 takes the ball-milled mixture and screens it, and screens out the mixture with a particle size of 13 μm to obtain the composite coating.

[0028] Weigh 1500g of a mixture with a particle size of 13μm into a plasma spray powder feeder and spray it on a platinum rod heated to 610℃. The specifications of the platinum rod are φ10mm×200mm, and the spraying thickness is 0.1mm. Transfer the platinum rod to a high-temperature furnace that has been heated to 500℃ in advance, heat it to 1050℃ at 3℃ / min, and keep it warm for 150min. After the insulation is completed, cool it to room temperature at a rate of 3℃ / h to obtain a platinum rod sprayed with a composite coating.

[0029] Examples 1-9

[0030] The formula of the composite coating of Examples 1-9 is shown in Table 1:

[0031] Table 1

[0032]

[0033] The formula of the composite coating of Comparative Examples 1-14 is shown in Table 2-3:

[0034] Table 2

[0035]

[0036] Table 3

[0037]

[0038] in:

[0039] The difference between Comparative Example 10 and Example 1 is that the particle size of the sieved mixture is 75 μm.

[0040] The difference between Comparative Example 11 and Example 1 is that the particle size of the sieved mixture is 0.3 μm.

[0041] The difference between Comparative Example 12 and Example 1 is that when spraying the composite coating, the temperature of the platinum rod is 310°C.

[0042] The difference between Comparative Example 13 and Example 1 is that when spraying the composite coating, the temperature of the platinum rod is 980°C.

[0043] The difference between Comparative Example 14 and Example 1 is that after spraying is completed, the platinum rod is not heated and kept warm.

[0044] Take a platinum rod coated with a composite coating and clamp it in the stirring device of a dynamic corrosion test furnace. The corundum crucible in the dynamic corrosion test furnace contains a glass sample. The glass can be commercially available substrate glass, cover glass or optical glass. Commercially available substrate glass is used in this experiment. Debug the stirring device so that the platinum rod is placed in the high-temperature molten glass during the stirring process. Set the heating program, and heat it to 1600°C at 5°C / min. After reaching the set temperature, keep it warm for 90 minutes, then start the stirring device at a speed of 15r / min, and use it continuously for 30 to 90 days. At the end of the test, raise the stirring device so that the platinum rod is not less than 20mm above the liquid level of the high-temperature molten glass. After power is turned off, cool it to room temperature, take the glass sample in the corundum crucible, and use an inductively coupled plasma mass spectrometer to test its Pt content in ppm; at the same time, use a polarizing microscope to observe whether there is Pt crystallization inside it. According to the above method, the glass samples after stirring with the platinum rods of Examples 1-9 and Comparative Examples 1-14 were tested and observed. The results are shown in Table 4-6:

[0045] Table 4

[0046]

[0047] Table 5

[0048]

[0049] Table 6

[0050]

[0051] It can be seen from Comparative Examples 1-2 that although the surface of the platinum rod is coated, due to the unreasonable design of the coating composition, there is obvious loss when tested after 30 and 90 days of operation.

[0052] The surface of the platinum rod in Comparative Example 3 was not coated, and it was found that after running for 30 days and 90 days under the same experimental conditions, its loss was extremely large.

[0053] Comparative Example 4 did not add yttrium oxide, Comparative Example 5 did not add cerium oxide, Comparative Example 6 did not add sodium oxide, and Comparative Example 7 did not add silicon dioxide. It was found that the platinum rod had obvious loss after running for 30 days and 90 days under the same experimental conditions. This is because the above four raw materials mainly play the role of stabilizer and modifier, which can make the sprayed protective film layer uniform and dense, thereby protecting the platinum rod body.

[0054] In Comparative Example 8, the sum of the mass percentages of Y2O3+CeO2 is 12.3%, resulting in excessive stabilizer content, which will lead to a reduction in the main component and thus cause the entire coating structure to be unstable, thereby failing to effectively protect the platinum rod body. In Comparative Example 9, the ratio of (Na2O+SiO2) / Y2O3 is 0.27, that is, the modifier content is too low, resulting in a low density of the network structure, thereby affecting the use effect of the coating.

[0055] The particle sizes of the mixed materials screened out in comparative examples 10-11 are 75 μm and 0.3 μm, respectively. Larger particle sizes will affect the uniformity of the coating, resulting in poorer use effects. Since there are certain requirements for coating thickness, using smaller particle sizes for spraying requires more layers to be sprayed, and the structural density between layers will also affect the use effect.

[0056] In Comparative Examples 12-13, the spraying temperatures of the coatings were 310°C and 980°C, respectively. Too low a temperature resulted in a large temperature difference between the coating and the platinum rod, which prevented the coating from achieving optimal density. Too high a temperature prolonged the curing time of the coating, which in turn affected the density of the coating. Comparative Example 14 did not perform a heat preservation treatment after the coating was sprayed, but directly cooled naturally, which resulted in the inability of the stabilizer and modifier to fully combine with the substrate, thereby affecting the structural stability, and cracks and flaking occurred during use.

[0057] In summary, the composite coating of the present invention, with zirconium oxide as the matrix, yttrium oxide and cerium oxide as stabilizers, sodium oxide and silicon dioxide as modifiers, is sprayed on the surface of platinum / platinum-rhodium alloy parts and operated at 1600°C for 30 days and 90 days respectively. It can be seen from the Pt content of the glass tested in Tables 4-6 and the defect morphology in the glass observed that coating the composite coating of the present invention can effectively avoid or reduce the generation of glass defects in the production process, while reducing the volatilization of platinum or platinum-rhodium alloy under high temperature conditions, thereby extending its service life and reducing production costs.

Claims

1. Suitable for composite coating of platinum or platinum-rhodium alloy, characterized in that: Calculated in terms of oxides, the composite coating includes the following components in percentage by mass: 82.5-97.5% ZrO2, 0.5-9.2% Y2O3, 0.3-8.7% CeO2, 0.5-2% Na2O, and 0.2-2.1% SiO2.

2. The composite coating suitable for platinum or platinum-rhodium alloy according to claim 1, characterized in that: The mass percentage of ZrO2 is 85-96%, the mass percentage of Y2O3 is 0.8-7.5%, the mass percentage of CeO2 is 0.5-6.1%, the mass percentage of Na2O is 0.7-1.6%, and the mass percentage of SiO2 is 0.5-1.5%.

3. The composite coating suitable for platinum or platinum-rhodium alloy according to claim 1, characterized in that: The mass ratio of the total mass of Na2O and SiO2 to that of Y2O3 is less than 1, and the sum of the mass percentages of Y2O3 and CeO2 is less than 10%.

4. The composite coating suitable for platinum or platinum-rhodium alloy according to claim 1, characterized in that: The particle size of each component is 1-30 μm.

5. The composite coating suitable for platinum or platinum-rhodium alloy according to claim 4, characterized in that: The particle size of each component is 3-15 μm.

6. The method for preparing a composite coating suitable for platinum or platinum-rhodium alloy according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1 weighs the raw materials and puts them into a mixer for thorough mixing; S2 weighs the fully mixed mixture, puts it into a material tank, uses grinding balls, drops anhydrous ethanol into it, and puts it into a ball mill for ball milling; S3 takes the ball-milled mixture and screens it to obtain a composite coating suitable for platinum or platinum-rhodium alloy.

7. The method for preparing a composite coating suitable for platinum or platinum-rhodium alloy according to claim 1, characterized in that: In step S2, the ball milling speed is 300-500 rpm, and the ball milling time is ≥120 min.

8. The use of the composite coating suitable for platinum or platinum-rhodium alloy according to any one of claims 1 to 5, characterized in that: The composite coating is sprayed onto the surface of the platinum or platinum-rhodium alloy part, and the temperature of the platinum or platinum-rhodium alloy part is 500-750°C.

9. The use of the composite coating suitable for platinum or platinum-rhodium alloy as claimed in claim 8, characterized in that: After spraying, the platinum or platinum-rhodium alloy parts are kept at 1000-1100°C for 140-160 minutes, and then cooled to room temperature at a rate of 2-3°C / h.

10. The use of the composite coating suitable for platinum or platinum-rhodium alloy as claimed in claim 8, characterized in that: The spraying thickness of the composite coating is 0.05-0.4mm.